Pendekatan SWOT dalam Strategi Pengembangan Usaha Keripik Kentang Bakti Rizky di Kota Padang (Meningkatkan Daya Saing Wilayah melalui Teknologi Pemasaran) - Fathinah Sifa Zahra Fathinah Sifa Zahra; Devi Analia; Widya Fitriana (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This research aims to analyze internal and external factors that affect the development of the potato chip business and formulate a strategy that can improve its performance. This research was conducted on February 16, 2024-March 16, 2024. This qualitative research uses case study observation and interview methods. Qualitative analysis will be done by describing the conditions and explaining the facts in the Bakti Rizky potato chip business in Padang City and the right strategy for the Bakti Rizky potato chip business. Quantitative analysis in this study is the calculation of IFE, EFE, and QSPM. The results showed that the strategic internal environment of Bakti Rizky's potato chip business in Padang City had strengths and weaknesses. In the external environment, namely opportunities and threats. The results of strategy formulation with SWOT analysis are as follows: (1) Maintaining affordable selling prices for all groups and increasing business scale through increasing production volumes accompanied by expanding product marketing by utilizing more modern technology (2) Increasing marketing efforts by utilizing information technology and cooperating with related agencies for training, promotion, packaging design, exhibitions and improving product quality through modern processing (3) Cooperate with raw material suppliers and increase consumer confidence by maintaining quality raw materials, despite the increase in raw material prices (4) Make product innovations in the form of attractive packaging and flavor variations such as spicy and cheese flavors to increase public buying interest and differentiate from competitors. The results of the QSPM analysis, which is a priority strategy, are increasing marketing efforts by utilizing information technology and collaborating with related agencies for training, promotion, packaging design, exhibitions, and improving product quality through modern processing.